Ekstraksi Kalium dari Abu Tandan Kosong Sawit Sebagai Katalis Pada Reaksi Transesterifikasi Minyak Sawit - Mohammad Imaduddin; Yoeswono Yoeswono; Karna Wijaya; Iqmal Tahir (Bulletin of Chemical Reaction Engineering & Catalysis, 2008)
Process of the transesterification reaction of palm oil with methanol by using ash of palm empty fruit bunches (EFB) as base catalyst has been conducted. The studied variables were effect of weight ash of EFB (5, 10, 15, 20, 25 g) and the molar ratio (3:1; 6:1; 9:1; and 12:1) of methanol to palm oil. Sample of ash was prepared through heating, screening, and reashing. A certain amount of ash was extracted in methanol with mixing for about 1 h at room temperature and the product was used as catlayst for transesterification process. The composition of the methyl esters (biodiesel) was analyzed using GC-MS and 1H NMR, whereas characters of biodiesel were analyzed using ASTM methods. The results of AAS analysis showed that potassium carbonate content in ash of EFB was 25.92% w/w. The main components of biodiesel were mixture of methyl palmitate and methyl oleat as the major compounds. The increasing of EFB ash weight (catalyst concentration) in reaction of transesterification enhanced the biodiesel conversion of 53.0; 76.9; 88.2; 90.5 and 97.8% (w/w) respectively. The increasing of the molar ratio of methanol to palm oil, the biodiesel conversion enhanced too, that were 74.0; 90.5; 92.3 and 98.8% (w/w) respectively. The properties of biodiesel were relatively conformed with specification of biodiesel (ASTM D 6751). © 2008 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)